María Cegarra Salcedo; Carmen Conde, Epistolario 1924-1988, edición, introducción y notas de Fran Garcerá, Madrid: Torremozas, 2018. Reseña. - Juárez López, Andrés (Revista de Escritoras Ibéricas, 2020)
Reseña de la obra